Integrated Biorefinery for Production of Biodegradable Film, Bioethanol, and Soda Pulp from Corn Stalks - Ömer Özyürek; Yalçın Çöpür (BioResources, 2023)
In traditional pulping, black liquor is burned in an alkali recovery system to produce energy. According to the integrated forest biorefinery (IFBR) concept, hemicellulose is partially pre-extracted prior to pulp production to generate value-added products. Corn stalks have a remarkable carbohydrate content (75% w/w), and thus were examined in this study in terms of the IFBR concept. The hemicelluloses were pre-extracted with hot water (90, 120, 135, and 150 °C), NaOH, and NaOH + NaBH4 (50, 70, and 90 °C) for 4 h. NaOH charges of 16.7, 26.7, and 33.3% were explored. The extracts were utilized to produce bioethanol and biodegradable films, and papermaking pulps were produced from the solid fractions. Differences among groups were identified via analysis of variance, and the Duncan’s test was applied to determine those differences that were significant. The results showed that the alkaline pre-extraction (26.7% NaOH at 50 °C) removed 35.6% of the xylose from the stalk structure. The liquid fraction collected from the hot water pre-extraction at 150 °C gave a 14.7% (g/100 g soluble material) yield of bioethanol. Moreover, the theoretical ethanol yield was calculated as 89.4%. The addition of gluten and nanocellulose to the xylan enabled the production of high-quality biodegradable films. Furthermore, the pulps produced from the hot water pre-extracted solid fractions were comparable in yield and pulp properties to the control soda pulp.